Bottom Water Acidification and Warming on the Western Eurasian Arctic Shelves: Dynamical Downscaling Projections. Issue 10 (25th October 2017) - Wallhead, P. J.; Bellerby, R. G. J.; Silyakova, A.; Slagstad, D.; Polukhin, A. A.
Abstract: The impacts of oceanic CO2 uptake and global warming on the surface ocean environment have received substantial attention, but few studies have focused on shelf bottom water, despite its importance as habitat for benthic organisms and demersal fisheries such as cod. We used a downscaling ocean biogeochemical model to project bottom water acidification and warming on the western Eurasian Arctic shelves. A model hindcast produced 14–18 year acidification trends that were largely consistent with observational estimates at stations in the Iceland and Irminger Seas. Projections under SRES A1B scenario revealed a rapid and spatially variable decline in bottom pH by 0.10–0.20 units over 50 years (2.5%–97.5% quantiles) at depths 50–500 m on the Norwegian, Barents, Kara, and East Greenland shelves. Bottom water undersaturation with respect to aragonite occurred over the entire Kara shelf by 2040 and over most of the Barents and East Greenland shelves by 2070. Shelf acidification was predominantly driven by the accumulation of anthropogenic CO2, and was concurrent with warming of 0.1–2.7°C over 50 years. These combined perturbations will act as significant multistressors on the Barents and Kara shelves. Future studies should aim to improve the resolution of shelf bottom processes in models, and should consider the Kara Sea and Russian shelves as possible bellwethers of shelf acidification. Key Points: Downscaling ocean model reproduces observed 14–18 year acidification trends (0.015–0.025 per decade) at high northern latitudes Shelf bottom acidification and warming under SRES A1B is rapid and spatially variable (0.10–0.20 pH and 0.1–2.7°C over 50 years) Acidification and warming may stress benthic and demersal organisms on the Norwegian, Barents, Kara, and East Greenland shelves